Can the Posterior Segment Findings of the Eye and Serum Microbiota Metabolites Be a Biomarker in Schizophrenia? - Keser, Sinem; Yildiz, Sevler; Aydin, Suleyman; Keles, Julide; Aksoy, Aziz; Emre, Elif (Mdpi, 2026)
Background and Objectives: In many neurodegenerative diseases, the pathological changes occurring in the central nervous system may be reflected in the periphery. The aim of this study was to examine the possible relationship between the retina, choroid, and nerve fibre layer thicknesses measured on optic coherence tomography (OCT) and the serum microbiota metabolite levels of trimethyl amine-N-oxide (TMAO), S-equol, Indoxyl sulphate (IS), and Maresin 1 (MaR1). Materials and Methods: This study included a total of 60 subjects, comprising 30 patients diagnosed with schizophrenia and a control group of 30 healthy individuals. A sociodemographic form was given to all the subjects and the Positive and Negative Syndrome Scale (PANSS) to the schizophrenia patients. The eye fundus was evaluated with OCT. A 5 mL blood sample was taken from the arm of each subject, and the microbiota metabolite levels of TMAO, S-equol, IS, and MaR1 were examined. Results: The retina nerve fibre layer (RNFL) analysis results showed that the RNFL superior (p = 0.016), inferior (p = 0.002), central choroid (p = 0.033), nasal choroid (p = 0.004), temporal choroid (p = 0.038), and TMAO (p = 0.001) values were significantly lower in the schizophrenia patients than in the control group. In the patient group, a significant negative correlation was determined between the RNFL temporal measurements and IS, as well as a significant positive correlation between the central choroid measurement and the nasal choroid and temporal choroid measurements and between the nasal choroid and temporal choroid measurements. A statistically significant positive correlation was seen between S-equol and TMAO. A significant negative correlation was seen between the MaR1 level and age and disease duration. Conclusions: The study results showed that fundus changes are associated with serum microbiota metabolite levels in schizophrenia patients. Therefore, these parameters may be considered potential exploratory biomarkers; however, their clinical applicability requires validation in larger longitudinal studies.
Keywords: schizophrenia; TMAO; S-equol; IS; MaR1; OCT; microbiota